Understanding why degrowth is absent from mitigation scenarios - Béatrice Cointe; Antonin Pottier (Revue de la Régulation)
The range of climate change mitigation scenarios in the IPCC reports frames the futures and policies that we deem possible. In the mitigation pathways produced by Integrated Assessment Models (IAM), economic growth is sustained throughout the century, as we show by surveying the GDP trajectories considered in the IPCC AR5 scenario database and in the more recent IAM literature. We unpack the reasons for IAM’s commitment to GDP growth, and seek to understand the quasi-absence of no-growth and degrowth scenarios. An overview of the current organisation of IAM research highlights the internal dynamics within the IAM community and the resulting coordination of choices. We then analyse the representation of economic growth in two IAMs, GCAM (exogenous growth) and WITCH (endogenous growth). From a technical point of view, degrowth scenarios could be considered, but the modelling teams have coordinated their work around growth scenarios. Ultimately, the absence of degrowth/no growth scenarios stems from the fact that, economic growth is largely conceived of and computed as a “natural” driver in IAM research, and not as an intervention point.